The Effectiveness of Classical Guidance with Reinforcement and Cooperative Play Techniques to Promote Prosocial Behavior - Farahmita, Farahmita; Puji Sugiharto, Dwi Yuwono; Awalya, Awalya (Universitas Negeri Semarang, 2021)
Students are expected to have high prosocial behavior. However, the fact shows that most of theirs are still low indicated by being less sensitive to friend’s conditions, being unsympathetic, having a low sense of charity, dishonesty, disrespecting others’ rights and welfare. Thus, this study attempted to examine the effectiveness of classical guidance with reinforcement technique, cooperative play technique, and the combination of reinforcement and cooperative play techniques to promote students’ prosocial behavior. Non-Equivalent Control Group Design was employed by involving 47 Junior High School students in grades VII, VIII, and IX. Once the analysis has been conducted, the Wilcoxon test showed that the classical guidance with both techniques were effective to promote prosocial behavior, namely reinforcement technique gained (Z = -3,25, p <0, 05), and cooperative play technique gained (Z = -2,27, p <0, 05). In the same way, the combination of those techniques was effective to promote students’ prosocial behavior by having the results of (Z = -3.40, p <0.05). To discover any differences in the effectiveness, the researchers used Kruskal Wallis test. This test revealed that the difference between the three techniques was v (x² = 7.67, p <0.05). These findings are expected to provide input for counselors by providing classical guidance services with reinforcement and cooperative play techniques to promote prosocial behavior.